THE EFFECTIVENESS OF STORYTELLING STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION AT SECOND GRADES OF MTs AL-MA’ARIF 1 KABUPATEN SORONG - Sudibyo, Doni; Wibowo, Ari; Hatam, Wa Riani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2018)
This research aimed to know the effectiveness of storytelling strategy to improve the students’ reading comprehension at second grades of MTs Al-Marif 1 KabupatenSorong. Storytelling was one of the good strategy in teaching learning process especially in teaching reading, because it can make the student was easier to understand about the text/story. In this research, the researcher used Quasi-experimental design. The subject of this research was VIIIC as experiment class that consist of 30 students: 16 males and 14 females, and VIIIB as control class that also consist of 30 students: 15 males and 15 females. The instruments were collected by using test (pre-test and post-test). The form of the test was essay and true false question. After giving the pre-test to students, the researcher gave the treatment and the steps in teaching learning process were: (1) the teacher divides the student into four groups, one group consist of 7-8 students; (2) the teacher divides the story of narrative text in each group; (3) teacher tell the story by using gesture, tone of voice and movement in the text/story; (4) after tell the story, teacher writes the questions the whiteboard; (5) teacher gave 15-20 minutes in every group to discuss the answer of the questions, then teacher ask one of students in each groups to read their answers. After giving the treatment, the researcher gave the post-test. The researcher used to analyze the result that the students got. Based on the finding in this research, the researcher can conclude that the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected or it can be said that Storytelling Strategy was effective to improve the student’s reading comprehension at the second grade of MTS Al-Ma’arif 1 KabupatenSorong. It was supported by the result which show that the value of was 2,356 and the value of from the df (58) on degree of significance of 5% was 2.00. It means that the value of is higher than the value of